Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Certainly! Let's solve the polynomial equation step-by-step.
Given polynomial equation:
[tex]\[x^3 - 2x^2 - x + 2 = 0\][/tex]
### Part a) Finding Potential Rational Solutions Using the Rational Root Theorem:
The Rational Root Theorem states that any potential rational root, \( \frac{p}{q} \), of the polynomial \(a_nx^n + a_{n-1}x^{n-1} + \ldots + a_1x + a_0 = 0\) must be such that:
- \(p\) is a factor of the constant term \(a_0\).
- \(q\) is a factor of the leading coefficient \(a_n\).
In this polynomial:
- The constant term \(a_0 = 2\).
- The leading coefficient \(a_n = 1\).
#### Factors of the constant term (\(a_0 = 2\)):
The factors of 2 are \( \pm1, \pm2 \).
#### Factors of the leading coefficient (\(a_n = 1\)):
The factors of 1 are \( \pm1 \).
#### Potential Rational Roots:
The potential rational roots \( \frac{p}{q} \) are given by:
[tex]\[ \frac{\text{factors of } 2}{\text{factors of } 1} \][/tex]
Thus, the potential rational roots are:
[tex]\[ \pm1, \pm2 \][/tex]
So, the potential rational solutions are:
\( -2, -1, 1, 2 \).
### Part b) Finding the Distinct, Actual Rational Solutions:
We need to test each potential rational root in the original polynomial to determine which ones are actual solutions.
Substitute each potential rational root into the polynomial \(x^3 - 2x^2 - x + 2\) to check if they satisfy the equation:
1. For \(x = -2\):
[tex]\[ (-2)^3 - 2(-2)^2 - (-2) + 2 = -8 - 8 + 2 + 2 = -12 \neq 0 \][/tex]
So, \(x = -2\) is not a solution.
2. For \(x = -1\):
[tex]\[ (-1)^3 - 2(-1)^2 - (-1) + 2 = -1 - 2 + 1 + 2 = 0 \][/tex]
So, \(x = -1\) is a solution.
3. For \(x = 1\):
[tex]\[ 1^3 - 2(1)^2 - 1 + 2 = 1 - 2 - 1 + 2 = 0 \][/tex]
So, \(x = 1\) is a solution.
4. For \(x = 2\):
[tex]\[ 2^3 - 2(2)^2 - 2 + 2 = 8 - 8 - 2 + 2 = 0 \][/tex]
So, \(x = 2\) is a solution.
### Conclusion:
The actual rational solutions to the polynomial equation \(x^3 - 2x^2 - x + 2 = 0\) are:
b) [tex]\( -1, 1, 2 \)[/tex].
Given polynomial equation:
[tex]\[x^3 - 2x^2 - x + 2 = 0\][/tex]
### Part a) Finding Potential Rational Solutions Using the Rational Root Theorem:
The Rational Root Theorem states that any potential rational root, \( \frac{p}{q} \), of the polynomial \(a_nx^n + a_{n-1}x^{n-1} + \ldots + a_1x + a_0 = 0\) must be such that:
- \(p\) is a factor of the constant term \(a_0\).
- \(q\) is a factor of the leading coefficient \(a_n\).
In this polynomial:
- The constant term \(a_0 = 2\).
- The leading coefficient \(a_n = 1\).
#### Factors of the constant term (\(a_0 = 2\)):
The factors of 2 are \( \pm1, \pm2 \).
#### Factors of the leading coefficient (\(a_n = 1\)):
The factors of 1 are \( \pm1 \).
#### Potential Rational Roots:
The potential rational roots \( \frac{p}{q} \) are given by:
[tex]\[ \frac{\text{factors of } 2}{\text{factors of } 1} \][/tex]
Thus, the potential rational roots are:
[tex]\[ \pm1, \pm2 \][/tex]
So, the potential rational solutions are:
\( -2, -1, 1, 2 \).
### Part b) Finding the Distinct, Actual Rational Solutions:
We need to test each potential rational root in the original polynomial to determine which ones are actual solutions.
Substitute each potential rational root into the polynomial \(x^3 - 2x^2 - x + 2\) to check if they satisfy the equation:
1. For \(x = -2\):
[tex]\[ (-2)^3 - 2(-2)^2 - (-2) + 2 = -8 - 8 + 2 + 2 = -12 \neq 0 \][/tex]
So, \(x = -2\) is not a solution.
2. For \(x = -1\):
[tex]\[ (-1)^3 - 2(-1)^2 - (-1) + 2 = -1 - 2 + 1 + 2 = 0 \][/tex]
So, \(x = -1\) is a solution.
3. For \(x = 1\):
[tex]\[ 1^3 - 2(1)^2 - 1 + 2 = 1 - 2 - 1 + 2 = 0 \][/tex]
So, \(x = 1\) is a solution.
4. For \(x = 2\):
[tex]\[ 2^3 - 2(2)^2 - 2 + 2 = 8 - 8 - 2 + 2 = 0 \][/tex]
So, \(x = 2\) is a solution.
### Conclusion:
The actual rational solutions to the polynomial equation \(x^3 - 2x^2 - x + 2 = 0\) are:
b) [tex]\( -1, 1, 2 \)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.